2003
DOI: 10.1157/13048847
|View full text |Cite
|
Sign up to set email alerts
|

El ayuno del Ramadán y una unidad de urgencias

Abstract: Introducción. Se define como fenómeno de Raynaud a los cambios intermitentes de la coloración cutánea distal: palidez y/o cianosis, seguidas de hiperemia reactiva. En España la prevalencia es aproximadamente del 3% en varones y del 5% en mujeres 1 . Se considera enfermedad de Raynaud cuando aparece el fenómeno sin una enfermedad que lo provoque. Es común en mujeres en las primeras décadas de la vida. El síndrome de Raynaud es la asociación del fenómeno de Raynaud a una enfermedad que lo produce, entre las que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Table 2 lists several main studies addressing the impact on burden and pattern of attendance to EDs, hospitalizations, and admissions to intensive care. 7 8 9 10 11 12 13 The salient findings of these and other studies are discussed below. 7 8 9 10 11 12 13 14 15 16 17 18 19 20…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Table 2 lists several main studies addressing the impact on burden and pattern of attendance to EDs, hospitalizations, and admissions to intensive care. 7 8 9 10 11 12 13 The salient findings of these and other studies are discussed below. 7 8 9 10 11 12 13 14 15 16 17 18 19 20…”
Section: Resultsmentioning
confidence: 87%
“…►Table 2 lists several main studies addressing the impact on burden and pattern of attendance to EDs, hospitalizations, and admissions to intensive care. [7][8][9][10][11][12][13] The salient findings of these and other studies are discussed below. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] One study from Qatar found that Ramadan was not associated with the change in patient age or the proportion of high-acuity cases.…”
Section: Historical Notementioning
confidence: 88%
See 2 more Smart Citations
“…Cuando está haciendo el Ramadán, es más frecuente el dolor abdominal que cuando no está en Ramadán, en que el motivo más frecuente suele ser más por infecciones respiratorias altas o por dolores osteo-musculares. Es importante en estas circunstancias de Ramadán adecuar el tratamiento prescrito a la situación especial que está viviendo el paciente musulmán y prescribir pautas en las que el fármaco se tenga que tomar cada 12 o cada 24 horas 16 .…”
Section: Consultas Médicas Urgentes Más Frecuentesunclassified